Nitric oxide levels in brain, liver, and gills of silver catfish (Rhamdia quelen) exposed to the antiparasitic eprinomectin - Serafini S.* (2020)
© 2020, Springer Nature B.V.Nitric oxide (NO) is a mediator and biomarker of pro- and anti-inflammatory processes. Excessive levels of NO for long periods have been associated with inflammation and tissue damage. The metabolism and synthesis of NO is usually measured indirectly, as metabolites and enzymes involved in reactions, often as the nitrite/nitrate (NOx) level. The aim of the present study was to measure the NOx levels in vital organs of juvenile silver catfish (Rhamdia quelen) exposed to various levels of eprinomectin in the water. The fish were exposed for 24 and 48 h to start concentration (0 h) of eprinomectin in water (0.0, 1.12, 1.80, and 3.97 μg/L). The eprinomectin concentrations in water were lower at 24 h (0.0, 0.85, 1.14, and 1.15 μg/L) and 48 h (0.0, 0.39, 0.69, and 1.28 μg/L), due to the process of eprinomectin metabolization. Subsequently, the fish were left for 48 h of recovery in eprinomectin-free water. NO levels were measured indirectly, as NOx levels in brain, liver, and gill tissue. Within 24 h of exposure, there was no significant increase in NOx levels in the organs evaluated at any of the concentrations tested. However, increases in NOx levels did occur at 48 h of exposure in all organs, particularly at the two highest concentrations of eprinomectin (1.80 and 3.97 μg/L). The transfer of fish to eprinomectin-free water did not result in reversal of NOx levels after 48 h of recovery, especially in fish that had been exposed to the two highest concentrations in the brain and liver tissues, and for the highest concentration in the gills. We conclude that silver catfish exposed to eprinomectin for up to 48 h present possible cerebral, hepatic, and branchial inflammatory process associated with increased tissue NOx levels, and that recovery for 48 h in water without antiparasitic is insufficient for the fish to recover from the poisoning.